The Student Nurses Written Works of Health Science Institute: Error Analysis in Syntactical and Morphological Category - Fitriani, Somariah (Universitas Muhammadiyah Surakarta, 2018)
The research aims to examine and analyze student nursesâ written works in term of syntax and morphology category. Twenty-six students of the third semester took an English presentation course, which focused on medical cases. The results have revealed that 186 error identifications were found consisting of 132 syntactical errors and 54 morphological errors.Â The students make errors in the types of article, preposition, parallel structure, the use of be, passive voice, word order, tenses, infinitive to, modal auxiliary and subject determiner in syntactical category. While in morphological error, they make errors in the plural form, subject verb agreement, comparative adjective and word form. Word order is as the most common language error in syntax category with 36 total errors or 19.35% out of 186.Â The second one is preposition with 26 total errors or 13.97%. While in morphology category, subject verb agreement is the most common one with 29 total errors or 15.59%. The second common one is word form with 13 total errors or 6.98%. It can be concluded that there are 132 (70.96%) of error identification in syntactical category and 54 error identifications or 29.04% in morphological category. In addition to its error identification in syntactical and morphological features, the research has found that the causes of studentsâ errors are due to intralanguage and interlanguage errors as it has some slightly differences between Bahasa Indonesia and English in term of grammatical structure. Â